Compliance with Procurement Processes and its Effect on Service Delivery: A Case of Selected Departments in Limpopo Province - Zitha, H. E.; Mamabolo, M. A.; Sebola, M. P. (International Conference on Public Administration and Development Alternatives 04 - 06 July 2018, Stellenbosch University, Saldahna Bay, South Africa, 2018)
Compliance with procurement processes has been at the centre stage of the findings and recommendations by Auditor-General of South Africa. This is necessitated by the fact that procurement has become a strategic function for the enhancement of service delivery in South Africa. This paper presents the findings on the study that investigated compliance with procurement processes and its effect on service delivery: a case of selected departments in Limpopo Province. The departments included in the study are: The Department of Education, Public Works, Roads and Infrastructure, Social Development and Economic Development, Environment and Tourism. The study used two paradigm of social research namely; qualitative and quantitative methods. Furthermore, for quantitative research method, questionnaires were used, whilst face-to-face interviews were used for qualitative method. The sampling strategy involved both purposive and random stratified sampling methods. In this regard the study focused on the sections responsible for the procurement function i.e. Demand and Acquisition Management units. The study revealed that government has made great strides with regard to the legislative and policy framework for enhancing compliance with procurement processes with the main focal point of improving the speed of delivering sustainable quality services to the people. Yet to be seen is translation of the great strides into the speedy delivery of quality service delivery expected by the citizenry. Furthermore, the study revealed that procurement officials agree that compliance with procurement process has an effect on service delivery. Political interference, conflict of interests were amongst the key issues that were raised by respondents as factors that negatively affect compliance with procurement process which have a gross effect on service delivery. Service delivery backlog and violent public service delivery protests were cited as issues attributable to failure to comply with procurement processes. Training and capacity building programmes introduced aimed at enhancing compliance with procurement processes, introduction of punitive measures and consequence management were mentioned as amongst other recommendations.
Journal article published in The 3rd Annual International Conference on Public Administration and Development Alternatives, 04 - 06 July 2018, Stellenbosch University, Saldahna Bay, South Africa
Keywords: Compliance; Procurement; Public finance; Supply Chain Management; Supply Chain Management; Public finance